HOW TO EFFECTIVELY PROTECT THE HUMAN BODY FROM THE HARMFUL INFLUENCE OF XENOESTROGENS AND OTHER ENDOCRINE DISRUPTORS: PREVENTIVE AND THERAPEUTIC PERSPECTIVES - Małgorzata Kuczek; Aleksandra Wiśniewska; Karolina Kasprzak; Zuzanna Rabczak; Julia Marek; Justyna Tasior; Mateusz Jasiński; Michał Szalach; Aleksandra Żywicka; Natalia Kaleta (International Journal of Innovative Technologies in Social Science, 2025)
Xenoestrogens constitute a group of endocrine-disrupting chemicals that, by mimicking or interfering with the actions of endogenous estrogens, can affect hormonal balance and reproductive function. Due to their widespread presence in the environment—including plastics, cosmetics, food, and everyday consumer products—complete avoidance of exposure is virtually impossible. However, studies indicate that proper education, lifestyle modifications, and dietary interventions can significantly reduce exposure to these compounds and the associated health risks. This article investigates various strategies for the prevention of xenoestrogen and other endocrine disruptors exposure, the reduction of existing body burdens of these chemicals. The effectiveness of dietary and behavioral interventions is discussed, such as avoiding canned foods and plastic products, as well as using personal care products free from phthalates, parabens, triclosan, and benzophenone-3, all of which have been shown to markedly decrease urinary levels of xenoestrogens and other endocrine disruptors. Therapeutic interventions are also presented, including the use of selected supplements and pharmacological agents such as Chlorella pyrenoidosa, cholestyramine, olestra, coenzyme Q10, melatonin, and multi-strain probiotics, which have demonstrated beneficial effects in reducing the concentrations of endocrine-active compounds and mitigating their toxic effects. These findings underscore the critical role of multifaceted approaches, combining preventative behavioral changes with targeted substance interventions, to effectively mitigate exposure and safeguard public health from ubiquitous endocrine-disrupting chemicals (EDCs).